In silico detection of dysregulated genes and molecular pathways in Alzheimer’s disease as basis for food restoring approach - Ilaria Petrignani; Alessandra Pasquo; Roberto Bei; Paolo Di Nardo; Felicia Carotenuto; Noemi Pappagallo; Daniele Fraternale; Maria Cristina Albertini; Laura Teodori (PeerJ)
Forty-eight million people worldwide suffer from dementia, often associated with the growth of the elderly population. There are also concerns about the younger population, where increasing acute and chronic abuse of alcohol and neurotoxic substances may contribute to brain damage and the early onset of dementia. Alzheimer’s disease (AD) accounts for 60% of dementia cases and most therapies used so far have been unsuccessful. Genetic, epigenetic and vascular factors contribute to the pathogenesis of AD. Among the epigenetic mechanisms, modulation of microRNA (miRs) plays an important role. To detect genes and pathways involved in AD, we performed an original bioinformatic analysis of published Alzheimer’s dysregulated miRs using MIcroRNA ENrichment TURned NETwork (MIENTURNET) followed by Reactome tools. The interrogation of these platforms allowed us to discover common putative genes (by MIENTURNET) targeted by the dysregulated miRs and the pathways in which the set of altered genes are involved (by Reactome tool). Our in silico analysis showed that the β-catenin phosphorylation cascade and Netrin-1 signalling, resulted as the most significant. Lastly, based on the assumption that food bioactive compounds (BC) modulate miRs, which in turn modulate dysregulated genes and pathways associated with AD, a literature search demonstrated that some BC are indeed able to modulate dysregulated pathways and genes. Curcumin, osthole, puerarin, xanthoceraside, sulforaphane, salvianolic acid A, resveratrol and andrographolide lead to upregulation of the Wnt/β-catenin pathway. Choline, methionine, folate and vitamin B6/B12 modulate the upregulation of the Netrin-1 pathway. In conclusion, our in silico analysis of miRs identified dysregulated genes and their associated pathways, paving interesting and new insights for diagnosis and for potential therapeutic interventions.